2018
DOI: 10.3389/fneur.2018.00999
|View full text |Cite
|
Sign up to set email alerts
|

High-Order Visual Processing, Visual Symptoms, and Visual Hallucinations: A Possible Symptomatic Progression of Parkinson's Disease

Abstract: Objective: To determine whether Parkinson disease (PD) patients with (VH) have different clinical characteristics and gray-matter volume than those with visual misperceptions (VM) or other visual symptoms (OvS).Background: The spectrum of visual complaints in PD is broad and complex.Methods: We conducted a retrospective chart review of 525 PD patients to identify the frequency of visual symptoms and the association with clinical and radiological features. Brain volumetric MRI data was analyzed using multivaria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 43 publications
2
10
2
Order By: Relevance
“…38 As with many other ophthalmologic symptoms, patients with PD generally do not report diplopia spontaneously, hence treating physicians should actively ask for double vision and other ophthalmologic symptoms. 39,40 In our study, 22% of patients reported visual hallucinations, compared with 30%-60% in previous studies. 41 This discrepancy may be caused by underreporting of visual illusions-having the feeling that someone is in the room or interpreting a shadow as a person-which were part of earlier studies, but not explicitly surveyed by the VIPD-Q.…”
Section: Discussioncontrasting
confidence: 65%
See 2 more Smart Citations
“…38 As with many other ophthalmologic symptoms, patients with PD generally do not report diplopia spontaneously, hence treating physicians should actively ask for double vision and other ophthalmologic symptoms. 39,40 In our study, 22% of patients reported visual hallucinations, compared with 30%-60% in previous studies. 41 This discrepancy may be caused by underreporting of visual illusions-having the feeling that someone is in the room or interpreting a shadow as a person-which were part of earlier studies, but not explicitly surveyed by the VIPD-Q.…”
Section: Discussioncontrasting
confidence: 65%
“…Patients with PD experienced more ophthalmologic symptoms across all domains than controls (p < 0.001), as reflected by a higher VIPD-Q total score among patients (median 10 [interquartile range (IQR) 13]) than controls (median 2 [IQR 5]; p < 0.001). Ophthalmologic symptoms interfered with daily activities in 68% (95% CI, 65-71) of patients, compared with 35% (95% CI, [29][30][31][32][33][34][35][36][37][38][39][40][41] of controls (p < 0.001).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In practice, autonomic disorders should therefore be systematically looked for in a context of mild cognitive disorder, particularly in the case of sicca syndrome, constipation, and rhinorrhea. The description of photophobia in Parkinson's disease was recently done but not in DLB [40]. In our study, the higher the number of core symptoms of DLB present, the higher the frequency of photophobia, with a maximum of 36.3% in the Pro-DLB group.…”
Section: Clinical Issuescontrasting
confidence: 50%
“…Recent models for visual hallucinations suggest combined impairment in perceptual and attentional networks that leads to altered balance between top‐down and bottom‐up processes . Perception and attention deficit, integrative, and attentional models suggest that production of unrestrained perceptual activity occurs when the attentional focuses are impaired, and the recruited prior perception of a scene is not disconfirmed or blocked by discrepant visual inputs.…”
Section: Anatomical Pathophysiological Overlaps and Mechanismsmentioning
confidence: 99%